2020
DOI: 10.1136/bmjresp-2019-000510
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and views of patients, carers and healthcare professionals on using modems in domiciliary non-invasive ventilation (NIV): a qualitative study

Abstract: BackgroundAdvances in technology means that domiciliary non-invasive ventilation (NIV) devices can be remotely monitored via modems in patients’ homes. Possible benefits and challenges of modem technology have yet to be established. This study explored the perspectives and experiences of patients, their carers and healthcare professionals (HCPs) on the addition of modem technology in managing home NIV.MethodsA qualitative study using a combination of focus groups for HCPs and interviews for carers/patients was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Moreover, health care practitioners mention that patients may feel they are constantly being watched, 13,18 with one study noting that this can potentially impact the patient–clinician relationship. 16 On the other hand, the health care practitioners in the study by Korpershoek et al 14 believed constant monitoring would enhance the relationship because patients will feel heard and supported by their health care practitioners through individualized care, which is in agreement with the patients’ reported perceptions. 33,34 …”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Moreover, health care practitioners mention that patients may feel they are constantly being watched, 13,18 with one study noting that this can potentially impact the patient–clinician relationship. 16 On the other hand, the health care practitioners in the study by Korpershoek et al 14 believed constant monitoring would enhance the relationship because patients will feel heard and supported by their health care practitioners through individualized care, which is in agreement with the patients’ reported perceptions. 33,34 …”
Section: Discussionmentioning
confidence: 74%
“…Mansell et al 16 recruited 12 health care practitioners to participate in being interviewed on the use of noninvasive ventilation (NIV) with a modem technology to monitor tidal volume, leak, respiratory rate, minute ventilation, patient-triggered breaths, achieved pressure, and compliance of patients diagnosed with chronic hypercapnic respiratory failure. The study found that modern technology was generally considered a feasible addition in managing home NIV that increases the patient’s access to care.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Home ventilator monthly downloads in 44 patients with chronic obstructive pulmonary disease suggested that elevated respiratory rate and percentage of patient-triggered breaths may help predict respiratory exacerbations ( 27 ). Patients, home caregivers, and clinicians reported favorable experience of cloud-based monitoring in a qualitative study ( 28 ).…”
Section: Evidence For Telemonitoringmentioning
confidence: 99%